Azadirone-Type Limonoids from the Fruit of Chisocheton lasiocarpus and Their Cytotoxic Activity Against MCF-7 Breast Cancer Lines - Erina Hilmayanti; Nurlelasari Nurlelasari; Dewa Gede Katja; Ace Tatang Hidayat; Sofa Fajriah; Akhmad Darmawan; Unang Supratman; Mohamad Nurul Azmi; Yoshihito Shiono (Universitas Jenderal Soedirman, 2022)
Limonoid is derivatives of triterpenoid compound that have a wide variety of structures due to various ring-opening, rearrangements, and high-degree of oxidation. Limonoid is known as compounds that have wide-range of biological activities, including anticancer activity. This research was aimed to determine the chemical structure and cytotoxic activity of limonoid in the n-hexane extract of Chisocheton lasiocarpus fruit. Dried powder of C. lasiocarpus fruit was extracted using methanol followed by fractionated using n-hexane, ethyl acetate, and n-butanol. Five azadirone-type limonoids, 6α-(acetoxy)-14β,15β-epoxyazadirone (1), dysobinin (2), 7α-acetylneotricilenone (3), 6α-O-acetyl-7-deacetylnimocinol (4), and 7α-hyroxyneotricilenone (5), were isolated from the n-hexane extract of Chisocheton lasiocarpus fruit. The chemical structure of all compounds was identified by spectroscopic analysis, including 1D, 2D-NMR, IR, UV and HR-TOF MS as well as by comparison with previous reported spectra data. Compounds 1-5 were investigated from this plant for first time. The cytotoxic activity of the isolated compounds against MCF-7 breast cancer line were examined and the results showed that 7α-hyroxyneotricilenone (5) showed the moderate activity with IC50 values of 53 μM